2010
DOI: 10.1007/s00383-010-2646-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of negative appendectomy in childhood obesity

Abstract: Suspected appendicitis in childhood obesity is associated with increased incidence of normal appendectomy. Active observation in hospital in very obese children may reduce the rate of normal appendectomy without increasing the incidence of complicated appendicitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…33 Contrary to our results, a recent large study found obesity associated with a high negative appendectomy rate. 34 The explanation for this discrepancy may in part lie in the relatively high imaging rate of our study population, including some of those with a high clinical suspicion of appendicitis. Many children with equivocal US were reimaged, as were those with discrepancies between US results and clinical findings.…”
Section: Discussionmentioning
confidence: 86%
“…33 Contrary to our results, a recent large study found obesity associated with a high negative appendectomy rate. 34 The explanation for this discrepancy may in part lie in the relatively high imaging rate of our study population, including some of those with a high clinical suspicion of appendicitis. Many children with equivocal US were reimaged, as were those with discrepancies between US results and clinical findings.…”
Section: Discussionmentioning
confidence: 86%
“…19 Furthermore, the low sensitivity and specificity of US in these children could lead to an increased rate of negative appendectomy. 20 Despite these limitations, the pediatric literature recommends US before CT scan in the workup of the patient with appendicitis. 18,21,22 Our data revealed that 99.3% of the patients studied received either an US or a CT scan to confirm appendicitis; only 2 children underwent appendectomy without preoperative imaging.…”
Section: Discussionmentioning
confidence: 99%
“…This modality became less commonly used as CT became more widespread in the setting of acute appendicitis [41]. While US specificity rivals that of CT [15,17,44], US accuracy is operator-dependent [19], and the results may be less reliable in pediatric patients with higher body mass index [45], although the latter is debated [46]. In fact, US may have an increased diagnostic accuracy in children with higher body mass index as fat stranding would theoretically be more visible in such patients [47]; this theory has not been systematically evaluated, however.…”
Section: Discussionmentioning
confidence: 99%